Acculturative stress, social supports and achievement motivation among Indonesian students in Malaysian universities - Sabrina, Fiona (2014)
Study on motivation, especially achievement motivation and social support impacting Indonesian students in Malaysia in term of acculturative stress factors is limited. Thus, the purpose of this research was to describe the experience of the acculturative stress among Indonesian graduate students who pursue higher education in Malaysian higher education institutions. The primary focus was on determining relationship between achievement motivation, social supports and acculturative stress. This study was carried out among 370 Indonesian graduate students (194 females and 176 males) who study in private and public universities in the Klang Valley. The study employed a survey design where data collection used questionnaire. The instruments used were Acculturative Stress Scale for International Students (ASSIS) created by Sandhu and Asrabadi (1994), the Achievement Motivation Scale (AMS) created by Ye and Hagtvet’s (1992) and the Multidimensional Scale of Perceived Social Support (MSPSS) created by Zimet, Dahlem, Zimet and Farley (1988). The statistical analyses employed were t-test and anova to determine the differences in motivation, social supports, and acculturative stress based on age and gender; Pearson’s correlation to determine the relationships between variables; and regression analysis to determine the factor that contribute to acculturative stress. The results of the study show that all students have high level of achievement motivation and medium level of social supports and acculturative stress. The results also show that there are no significant differences in social support, motivation and acculturative stress based on gender. On the other hand, there are signification correlations between acculturative stress and achievement motivation (negative correlations) and social support (positive correlation). In term of factor contributing to acculturative stress, the finding shows that demographic background as predictors acculturative stress. The finding described that age, length of stay and funding were significant predictors acculturative stress in the acculturation process. Thus, achievement motivation and social supports affected in the role of acculturative stress Indonesian students level. Finally, this study is to help Indonesian students to manage stressors during the acculturation process while studying in Malaysia.